Intrarater and interrater reliability of the Anteromedial Reach Test in healthy participants - Bent NP; Rushton AB; Wright CC; Petherick EJ; Batt ME (Dove Medical Press, 2014)
Nicholas P Bent,1 Alison B Rushton,1 Chris C Wright,1 Emma-Jane Petherick,2 Mark E Batt3 1School of Sport, Exercise and Rehabilitation Sciences, University of Birmingham, Birmingham, 2School of Health and Life Sciences, Glasgow Caledonian University, Glasgow, 3Centre for Sports Medicine, Nottingham University Hospitals, Nottingham, UK Background: The Anteromedial Reach Test is a performance-based outcome measure for evaluating dynamic knee stability in patients with anterior cruciate ligament injury. No previously published study has adequately evaluated intrarater or interrater reliability of the Anteromedial Reach Test, so the purpose of this study was to assess these measurement properties in healthy participants prior to their investigation in patients with anterior cruciate ligament injury. Methods: Two raters (A and B) tested 39 healthy university staff and students (20 men, 19 women). For the intrarater reliability investigation, rater A tested participants on three separate test occasions (days 1, 2, and 3) at the same time of day. For the interrater reliability investigation, raters A and B independently tested participants on the same test occasion (day 3). Results: There was no significant systematic bias between test occasions or raters. Values of the intraclass correlation coefficient (2,1) were 0.96 for intrarater reliability of both the dominant leg and nondominant leg and 0.97 (dominant leg) and 0.98 (nondominant leg) for interrater reliability. Values for the standard error of measurement were 1.46 (dominant leg) and 1.62 (nondominant leg) for the intrarater investigation, and 1.26 (dominant leg) and 1.04 (nondominant leg) for the interrater investigation. At the 90% confidence level, the minimum detectable change was 3.8% and the error in an individual's score at a given point in time was ±2.7%. Conclusion: The Anteromedial Reach Test demonstrated excellent intrarater and interrater reliability in healthy participants. This provides a basis for future investigation of the measurement properties of the Anteromedial Reach Test in patients with anterior cruciate ligament injury. Keywords: anterior cruciate ligament, injury, dynamic stability, rehabilitation, outcome measures